Financial institutions' reporting requirements and the criteria for a good tax system - Kontkanen, Erkki; Lindgren, Juha (Routledge, 2022)
In order to ensure an adequate information base in the taxation, there has been in recent years increasing efforts to use information obtained from third parties, in particular from banks and financial institutions in general. The additional reporting duties imposed on taxpayers and financial institutions offer new tools for the prevention of the tax avoidance as well as for collecting taxation information. However, the new reporting requirements can also be seen as increasing regulatory complexity and interpretability, which cause administrative burden. This chapter examines this development especially on the light of the criteria for a good tax system. From the taxpayer's point of view, a good tax system emphasizes safeguarding the taxpayer's rights. From the tax recipient's point of view, a tax procedure must guarantee a fiscal return. The role of financial institutions and the diversity of tasks have increased rapidly in the development of the tax procedure. It is therefore appropriate to look at the criteria for a good tax system from the perspective of the financial institutions as third-party notifiers.
Keywords: fi=Talousoikeus|en=Business Law|